2010
DOI: 10.1002/elan.200900533
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fe2+ and Fe3+ in Aqueous Solutions Containing Food Chelators by Differential Pulse Anodic Stripping Voltammetry

Abstract: The objective was to investigate interactions between iron and food chelators in an aqueous environment. The net complexation were investigated by DPASV in a NaClO 4 electrolyte using a platinum electrode. The experimental conditions were simulating the environment of the human duodenum. The results indicated a net coordination affinity between Fe 2þ and the organic acids in the following order; ascorbic acid % phytate > pyruvate > lactate > acetate. For Fe 3þ net complexation, the stability was in the order o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…2 ). In previous studies on fermented carrot juice, we observed an increase in available ferric iron but, in contrast to the present study, did also observe a decrease in available ferrous iron in fermented carrot juice compared to fresh carrot juice [ 20 ]. However, the carrot juices were not exposed to simulated gastrointestinal digestion as the vegetables were in the present study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…2 ). In previous studies on fermented carrot juice, we observed an increase in available ferric iron but, in contrast to the present study, did also observe a decrease in available ferrous iron in fermented carrot juice compared to fresh carrot juice [ 20 ]. However, the carrot juices were not exposed to simulated gastrointestinal digestion as the vegetables were in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…The pH of the electrolyte was kept at 4.0 to simulate the pH of the proximal part of the duodenum [ 19 ]. The method for running food samples (fermented carrot juices) was described previously [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 But its deficiency or overload can induce serious disorders and infectious diseases such as anemia, 2 hemochromatosis, 3 malaria, 4 Parkinson, 5 Alzheimer. 6 Many techniques for detecting Fe 3+ have been reported, including atomic absorption spectrometry, 7,8 voltammetry, 9 fluorometric and colorimetric method. [10][11][12][13] Many are complicated and not suitable for quick and online monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the most plausible explanation is that free iron transported inside the cells produced an increase in ROS, which in turn internalised DMT-1 and reduced iron uptake. However, by complexing/binding ferrous iron [ 25 ] or neutralising free radicals [ 23 ], AA is likely to have prevented the intracellular environment from further oxidation, resulting in the increase in iron uptake. Therefore, all the above suggests that AA could enhance iron uptake not only through an increase in soluble iron but also through intracellular redox mechanisms that are DMT-1 dependent.…”
Section: Discussionmentioning
confidence: 99%